Climate changes and their influences in water balance of Pantanal biome - de Oliveira Aparecido, Lucas Eduardo; Lorençone, Pedro Antonio; Lorençone, João Antonio; de Meneses, Kamila Cunha [UNESP]; da Silva Cabral de Moraes, Jose Reinaldo (Springer Nature, 2021)
Climate change is a major problem for humanity, as it can drastically alter the current climate scenario, affecting mainly agriculture. In the state of Mato Grosso do Sul (MS), agribusiness is the main economic activity representing a large part of the state’s GDP. Therefore, the aim of this study was to evaluate the influence of climate change on the climatological water balance in the Pantanal regions of Brazil. We used a 30-year historical series (1987–2018) of air temperature data (Tar, °C) and rainfall (P, mm) from the state of MS; climatic data were collected by the National Aeronautics and Space Administration platform/Prediction of World Wide Energy Resources - (NASA/POWER). Potential evapotranspiration (PET) was estimated using the Camargo (1971) method. The water balance (WB) was calculated using the Thornthwaite and Mather (1955) method, with soil water storage capacity equal to 100 mm. We calculated the aridity, hydric, and moisture indices for all municipalities in MS, and later classified according to Thornthwaite (1948). The scenarios used were based on the (IPCC 2014) projections. Air temperatures in the MS ranged from 22.5 to 27.6 °C in the current scenario; rainfall and PET have an average of 1400 mm annual−1 and 1188 mm annual−1, respectively. The WB of the state of MS has an EXC and DEF of 197.7 mm annual−1 and 64.2 mm annual−1, respectively. The predominant climatic type is C2 - subhumid. The highest values for SWS and EXC occur in scenarios S5, S10, S15, and S20, which are the most moisture scenarios. The highest DEF occurred in scenarios S1, S11, S16, and S21; these scenarios showed the driest climatic types. The northwestern region of the state, where the Pantanal is located, was the driest. In scenario S21, the climate of the state has a drastic change that makes several crops in the MS unfeasible, thus negatively influencing the fauna and flora of the Pantanal biome.